(untitled) (Journal of Namibian Studies : History Politics Culture, 2024)
The cinema has addressed the subject of French nuclear tests in Algeria, which took place between 1960 and 1966, as part of historical and political narratives. These events have been transformed into dramatic and artistic material, revealing their tragic aspects and their impact on the Algerian people and the environment. Through artistic visions that merge fiction with reality, filmmakers have created narratives that simulate the destructive effects of these tests, focusing on their environmental and human repercussions. Global cinema has also represented the nuclear bomb in various films, tackling political and social concerns associated with nuclear wars. These films offer diverse perspectives on the widespread destruction caused by nuclear weapons from different angles. This article begins by examining whether films addressing the topic of nuclear bombs constitute an independent genre or fall within existing cinematic categories, such as war films or science fiction. It then explores the representation of the effects of nuclear bombs in global cinema, as well as how French nuclear tests in Algeria have been depicted in both fictional and documentary films.